Implementasi Pola Pengelolaan Keuangan Badan Layanan Umum Daerah (PPK-BLUD) Dan Kualitas Layanan Terhadap Kepuasan Pasien: (Studi Pada Rawat Inap Paviliun Tandang Rumah Sakit Umum Daerah Kabupaten Sumedang) - Deni istiono (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
This study was conducted to obtain a description of the Implementation of the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD) and Service Quality and Patient Satisfaction at the Sumedang District General Hospital, Tandang Pavilion. The type of research is descriptive and verification. The population of this study were patients in the Away Pavilion of the Sumedang Regency General Hospital who were inpatients of the Antang Pavilion of the Sumedang Regency General Hospital for 1 month, counted as many as 250 people. determine the sample by random or random (probability sampling), with the simple random sampling method, that is, each population has the same possibility of selection, the results of the calculation of the sample taken are 95 patients. Based on the results of the study, it was obtained testing the Main Hypothesis of the Effect of the Regional Public Service Agency of Sumedang Regency and Service Quality on Patient Satisfaction. The results of the test, obtained the decision H0 was rejected, so that the variables of the Regional Public Service Agency of Sumedang Regency and Service Quality on Patient Satisfaction were accepted. The significance of the value of the test results is also supported by the magnitude of the value of the Coefficient of Determination. This value indicates that the Regional Public Service Agency of Sumedang Regency and the Quality of Service have an effect on Patient Satisfaction. while the rest is influenced by other variables. Sub-Hypothesis Testing of the Effect of Regional Public Service Agencies on Patient Satisfaction To answer the proposed hypothesis, a test is carried out, namely by using path analysis testing. Based on the test results obtained path coefficient values. To find out more about the effect of Regional Public Service Agency variables on Patient Satisfaction, a test was carried out, the test results obtained that the tcount value was greater than the ttable value. To find out more about the effect of the Regional Public Service Agency variable on patient satisfaction, a test was carried out, namely by looking at the comparison between tcount and ttable. Based on the test, the value of tcount is greater than the value of ttable, namely tcount. From the results of these calculations, the decision Ho is rejected, so that the Regional Public Service Agency variable affects the patient satisfaction variable.